EFEK DOCTOR'S QUALITY OF CARE TERHADAP WORD OF MOUTH DAN REVISITED PATIENT YANG DIMEDIASI OLEH PATIENT SATISFACTION - Wiwik Mayanti (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2008)
A doctor must strive to provide health care as best as they could in order to create satisfied patient. The objective of this research is to investigate the effect of quality of care from the doctor and patient satisfaction in hospital, clinic. And the effect of patient satisfaction on word of mouth, then patient satisfaction can create revisited patient. A theoretical framework was developed to test the relationship among the study construct. The design of this research applies to hospital, clinic and the questionnaires were spread away to 100 respondents or patients from 2 hospital in Jakarta, bekasi and by using purpose sampling. The result of the research conclude that doctor's quality of care has a significant effect to patient satisfaction, and patients satisfaction hasn't a significant effect to word of mouth but patient satisfaction has a significant effect to revisited patient.Keyword: doctor's quality of care, patient satisfaction, word of mouth, revisited patient.